Psychosocial Impact of Lockdown Due to Novel Corona Virus Covid 19 among Medical Undergraduate Students - Rupali Sarode; Shashank Gotarkar; Prakash Mohite; Sourya Acharya; Samarth Shukla (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The outbreak of Novel Corona Virus Disease (COVID-19) which started in the late 2019,in Wuhan in Hubei province of China because of its high infectivity and fatality rate, has caused universalpsychosocial impact on people Mass fear of COVID-19, termed as “Coronaphobia”, has generated a plethoraof psychiatric manifestations across the different strata of the society. So, this study has been undertaken todefine psychosocial impact of COVID-19 on Medical graduants with an objective to assess the reasons forbreaking the lockdown and the level of psychosocial impact of lockdown on a Medical graduants duringthe COVID-19 lockdown period. A cross sectional prospective study was done on 285 students of First tofinal year MBBS Validated Psychosocial Impact Scale was used for data collection. The results showedthe intensity of negative impact of lockdown on the students studying in medical college. 18.60% studentsshowed normal response to the lockdown situation in this COVID 19 pandemic. 47.72% students showedborderline negative impact of lockdown. 29.12 students had mild negative impact, 4.56 % students hadmoderate negative impact and no student found to be in range of severe negative impact of lockdown.